Taxonomic notes on some Brazilian species of Synalpheus Spence Bate, 1888, with new records and description of a new species (Decapoda, Alpheidae) - Anker, Arthur; Pachelle, Paulo P.g. (Zootaxa, 2014)
The present report deals with several western Atlantic species of the snapping shrimp genus Synalpheus Spence Bate, 1888 occurring in Brazilian territorial waters. Two species, Synalpheus cf. ruetzleri Macdonald & Duffy, 2006 and Synalpheus yano (Ríos & Duffy, 2007), are recorded from the southwestern Atlantic Ocean and Brazil (Ceará) for the first time; S. yano is also newly reported from the eastern Gulf of Mexico and USA (Florida). Synalpheus androsi Coutière, 1909, a distinctive species previously known in Brazil only from a single unconfirmed record, is confirmed to be present in Brazilian waters based on material from Bahia and Espírito Santo. Synalpheus tenuispina Coutière, 1909, a poorly known species from southern Brazil, is redescribed. Synalpheus ul (Ríos & Duffy, 2007), previously known from Bahia and Alagoas, is reported from Pernambuco based on older “Calypso” material misidentified as Synalpheus longicarpus (Herrick, 1891). A new species from the Synalpheus paraneptunus Coutière, 1909 complex is described as Synalpheus maxillispinus sp. nov. based on three specimens dredged from moderate depths (15–55 m) off southern Bahia and Espírito Santo, eastern Brazil. Finally, an incomplete specimen that appears to belong to a species presently unknown in Brazil is preliminarily reported as Synalpheus sp. gambarelloides group. Illustrations are provided for all reported taxa except for S. ul.